The Use of ex Vivo Rodent Platforms in Neuroscience Translational Research With Attention to the 3Rs Philosophy - Lossi, Laura; Merighi, Adalberto (Frontiers in Veterinary Science, 2018)
The principles of the 3Rs - Replacement, Reduction and Refinement - are at the basis of most advanced national and supranational (EU) regulations on animal experimentation and welfare. In the perspective to reduce and refine the use of these animals in translational research, we here discuss the use of rodent acute and organotypically cultured central nervous system (CNS) slices. We describe novel applications of these ex vivo platforms in medium-throughput screening of neuroactive molecules of potential pharmacological interest, with particular attention to more recent developments that permit to fully exploit the potential of direct genetic engineering of organotypic cultures using transfection techniques. Finally, we consider a series of new approaches and perspectives that will be of relevance to broaden the use of ex vivo platforms under the 3Rs philosophy.